[RuV(NCN-Me)(bpy)(O)]3+ Mediates efficient C–H bond oxidation from NADH analogs in aqueous media rather than water oxidation. Issue 3 (5th December 2014) - Patel, Jully; Majee, Karunamay; Ahmạd, Ejaz; Tanaka, Koji; Padhi, Sumanta Kumar
Abstract : The [Ru V O] 3+ and [Ru VI O] 4+ generated from [Ru II (NCN-Me)(bpy)(H2 O)](PF6 )2 play the selective role in C–H bond oxidation of 2-(pyridin-2-yl)-9, 10-dihydroacridine (PADHH) and water splitting, respectively, are reported. Abstract : [Ru V O] 3+ and [Ru VI O] 4+ generated from [Ru II (NCN-Me)(bpy)(H2 O)](PF6 )2 (where NCN-Me is the neutral N -methyl-3, 5-di(2-pyridyl)pyridinium iodide after deprotonation of the C–H bond) play a selective role in the C–H bond oxidation of 2-(pyridin-2-yl)-9, 10-dihydroacridine (PADHH) and water oxidation, respectively.